Asymptomatic Wilson’s Disease Diagnosed during the Course of Ulcerative Colitis: A Case Report and Review - Megumi Kinjo; Shintaro Sagami; Akira Nogami; Kanade Serizawa; Shunsuke Shibui; Satoko Umeda; Kunio Asonuma; Hidetsugu Saito; Masaru Nakano; Toshifumi Hibi; Taku Kobayashi (Inflammatory Intestinal Diseases)
Introduction: While previous reports have suggested an association between Wilson’s disease (WD) and ulcerative colitis (UC), we present the first case of asymptomatic WD diagnosed during the treatment course of UC. Case Presentation: A 14-year-old male receiving treatment for UC developed elevated liver enzymes without any related symptoms. After ruling out drug-induced liver toxicity and other possible causes of hepatitis, further investigation was initiated due to his sister’s subsequent diagnosis of WD. Tests revealed low serum ceruloplasmin and ATP7B gene variants, confirming WD. Following zinc therapy, liver enzymes have been normalized, and his previously refractory UC became under control. Conclusion: This case raises important questions about potential pathophysiological interactions between the two diseases.